| library test /*isNonNullableByDefault*/; |
| import self as self; |
| import "dart:core" as core; |
| |
| class A extends core::Object { |
| synthetic constructor •() → self::A |
| : super core::Object::•() |
| ; |
| } |
| class B extends self::A { |
| synthetic constructor •() → self::B |
| : super self::A::•() |
| ; |
| operator +(self::C v) → self::B |
| return throw ""; |
| operator -(core::int i) → self::B |
| return throw ""; |
| operator *(self::B v) → self::B |
| return throw ""; |
| operator &(self::A v) → self::C |
| return throw ""; |
| } |
| class C extends self::B { |
| synthetic constructor •() → self::C |
| : super self::B::•() |
| ; |
| } |
| class Test extends core::Object { |
| field self::B member; |
| field self::B? member2 = null; |
| constructor •(self::B member) → self::Test |
| : self::Test::member = member, super core::Object::•() |
| ; |
| static method test(self::Test t) → void { |
| t.{self::Test::member} = self::f<self::B>(); |
| let final self::Test #t1 = t in #t1.{self::Test::member2}{self::B?} == null ?{self::B?} #t1.{self::Test::member2} = self::f<self::B?>() : null; |
| let final self::Test #t2 = t in #t2.{self::Test::member} = #t2.{self::Test::member}{self::B}.{self::B::+}(self::f<self::C>()){(self::C) → self::B}; |
| let final self::Test #t3 = t in #t3.{self::Test::member} = #t3.{self::Test::member}{self::B}.{self::B::*}(self::f<self::B>()){(self::B) → self::B}; |
| let final self::Test #t4 = t in #t4.{self::Test::member} = #t4.{self::Test::member}{self::B}.{self::B::&}(self::f<self::A>()){(self::A) → self::C}; |
| let final self::Test #t5 = t in #t5.{self::Test::member} = #t5.{self::Test::member}{self::B}.{self::B::-}(1){(core::int) → self::B}; |
| let final self::Test #t6 = t in #t6.{self::Test::member} = #t6.{self::Test::member}{self::B}.{self::B::-}(1){(core::int) → self::B}; |
| self::B v1 = t.{self::Test::member} = self::f<self::B>(); |
| self::B? v2 = let final self::Test #t7 = t in let final self::B? #t8 = #t7.{self::Test::member2}{self::B?} in #t8 == null ?{self::B?} #t7.{self::Test::member2} = self::f<self::B?>() : #t8{self::B}; |
| self::B v3 = let final self::Test #t9 = t in #t9.{self::Test::member} = #t9.{self::Test::member}{self::B}.{self::B::+}(self::f<self::C>()){(self::C) → self::B}; |
| self::B v4 = let final self::Test #t10 = t in #t10.{self::Test::member} = #t10.{self::Test::member}{self::B}.{self::B::*}(self::f<self::B>()){(self::B) → self::B}; |
| self::C v5 = let final self::Test #t11 = t in #t11.{self::Test::member} = #t11.{self::Test::member}{self::B}.{self::B::&}(self::f<self::A>()){(self::A) → self::C}; |
| self::B v6 = let final self::Test #t12 = t in #t12.{self::Test::member} = #t12.{self::Test::member}{self::B}.{self::B::-}(1){(core::int) → self::B}; |
| self::B v7 = let final self::Test #t13 = t in let final self::B #t14 = #t13.{self::Test::member}{self::B} in let final self::B #t15 = #t13.{self::Test::member} = #t14.{self::B::-}(1){(core::int) → self::B} in #t14; |
| } |
| } |
| static method f<T extends core::Object? = dynamic>() → self::f::T% |
| return throw ""; |
| static method main() → dynamic {} |